Bioactive compounds and antioxidant activity in tropical fruits grown in the lower-middle São Francisco Valley - Batista, Patrício; de Lima, Maria Auxiliadora; Alves, Ricardo; Façanha, Rafaela (Revista Ciência Agronômica, 2018)
The aim of this study was to evaluate the levels of bioactive compounds and antioxidant activity in fruit of commercial cultivars of mango, acerola, guava, atemoya and custard apple produced in the lower-middle São Francisco Valley, with a view to adding value to the product because of their functional properties. Fruits harvested in commercial areas of the region were evaluated for levels of ascorbic acid, total anthocyanins, yellow flavonoids, total carotenoids and total extractable polyphenols, and for total antioxidant activity, using the ABTS and ORAC methods. The data were submitted to descriptive statistical analysis. All the fruits under evaluation presented levels of bioactive compounds and antioxidant activity, especially the acerola, and in particular the Sertaneja and Okinawa cultivars, which may be considered excellent sources of natural antioxidants, with their consumption encouraged as part of a healthy diet. The significant positive correlation found between antioxidant activity and the levels of ascorbic acid, anthocyanins, yellow flavonoids, carotenoids and total extractable polyphenols with the two methods employed, shows that for the fruits under evaluation, this activity was influenced by the determined set of bioactive compounds.